2023
DOI: 10.1021/acs.analchem.2c02950
|View full text |Cite
|
Sign up to set email alerts
|

Periodic Photobleaching with Structured Illumination for Diffusion Imaging

Abstract: The use of periodically structured illumination coupled with spatial Fourier-transform fluorescence recovery after photobleaching (FT-FRAP) was shown to support diffusivity mapping within segmented domains of arbitrary shape. Periodic "comb-bleach" patterning of the excitation beam during photobleaching encoded spatial maps of diffusion onto harmonic peaks in the spatial Fourier transform. Diffusion manifests as a simple exponential decay of a given harmonic, improving the signal to noise ratio and simplifying… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(16 citation statements)
references
References 40 publications
0
3
0
Order By: Relevance
“…These observations are in contrast to prior FT-FRAP studies of ritonavir in PVPVA, following water vapor exposure, in which substantial contributions from interfacial exchange were recorded. 23 The differences are tentatively attributed to differences in glass transition temperatures, T g , for the two active pharmaceutical ingredients. Whereas T g is well below ambient temperatures of 20 °C for ibuprofen (−42 °C), it is substantially above for ritonavir (50 °C).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…These observations are in contrast to prior FT-FRAP studies of ritonavir in PVPVA, following water vapor exposure, in which substantial contributions from interfacial exchange were recorded. 23 The differences are tentatively attributed to differences in glass transition temperatures, T g , for the two active pharmaceutical ingredients. Whereas T g is well below ambient temperatures of 20 °C for ibuprofen (−42 °C), it is substantially above for ritonavir (50 °C).…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…In beam-scanning confocal microscopes, we have shown previously that integration of FT-FRAP with comb-bleach illumination simply requires software/firmware updates to the slow-scan mirror used to direct the beam across the FoV during the imaging and photobleaching stages, with no required changes to the physical hardware at all. 23 In this work, relatively minor retrofitting of a commercial wide-field microscope with a focal plane array detector was performed by a relatively straightforward addition of the DOE to the beam path and an upgrade to the photobleach laser source. These two microscope designs (confocal beam-scanning and wide field detection with a focal plane array) collectively comprise the overwhelming bulk of systems routinely used for fluorescence microscopy, and correspondingly, for FRAP analysis.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…Single particle tracking (SPT) has been extensively applied to extract high-spatiotemporal information of molecular diffusion. However, SPT measurements can be limited by the capabilities of tracking software analyses used to analyze the data that can include challenges of emitters that cross paths, photoblink, or have low signal. These challenges can result in a limited capability to detect and track particles moving at very high speeds for multiple consecutive frames or in complex matrices. , Finally, other optical techniques designed to measure the diffusion coefficients, such as fluorescence recovery after photobleaching (FRAP), require much larger length scales (∼10–100 μm 2 ) for accurate imaging. Moreover, FRAP extracts an average diffusion coefficient over the entire area, but provides no local diffusion information.…”
Section: Introductionmentioning
confidence: 99%
“…22 Following the initial demonstration, FT-FRAP has recently been applied to characterize the mobility and chemical composition of phase-separated microdomains in amorphous pharmaceutical formulations. 23 In FT-FRAP, a periodic line bleach is achieved by controlling fast-scanning mirrors (either resonant or galvanometer scan mirrors) that rapidly translate the excitation beam across the FoV. In this implementation, a significant reduction in local heating is achieved by distributing the incident power along multiple equally separated rapidly scanned lines.…”
Section: ■ Introductionmentioning
confidence: 99%
“…Several previous studies have demonstrated the use of line and patterned illumination profiles to circumvent some of the limitations of conventional FRAP analysis. Recently, Geiger et al have demonstrated the theoretical framework and proof-of-concept experiments for Fourier-transform FRAP (FT-FRAP) with a comb-bleaching pattern across a large (∼1 × 1 mm) field of view (FoV) . Following the initial demonstration, FT-FRAP has recently been applied to characterize the mobility and chemical composition of phase-separated microdomains in amorphous pharmaceutical formulations . In FT-FRAP, a periodic line bleach is achieved by controlling fast-scanning mirrors (either resonant or galvanometer scan mirrors) that rapidly translate the excitation beam across the FoV.…”
Section: Introductionmentioning
confidence: 99%